Aspirin use and the risk of cholangiocarcinoma3. Issue 3 (26th April 2016) - Choi, Jonggi; Ghoz, Hassan M.; Peeraphatdit, Thoetchai; Baichoo, Esha; Addissie, Benyam D.; Harmsen, William S.; Therneau, Terry M.; Olson, Janet E.; Chaiteerakij, Roongruedee; Roberts, Lewis R.
Abstract : Whether aspirin use is protective against cholangiocarcinoma (CCA) remains unclear. We determined the association between aspirin use and other risk factors for each CCA subtype individually. In a hospital‐based case‐control study, 2395 CCA cases (1169 intrahepatic, 995 perihilar, and 231 distal) seen at the Mayo Clinic, Rochester, MN, from 2000 through 2014 were enrolled. Controls selected from the Mayo Clinic Biobank were matched two to one with cases by age, sex, race, and residence (n = 4769). Associations between aspirin use, other risk factors, and CCA risk were determined. Aspirin was used by 591 (24.7%) CCA cases and 2129 (44.6%) controls. There was a significant inverse association of aspirin use with all CCA subtypes, with adjusted odds ratios (AORs) of 0.35 (95% confidence interval [CI], 0.29‐0.42), 0.34 (95% CI 0.27‐0.42), and 0.29 (95% CI 0.19‐0.44) for intrahepatic, perihilar, and distal CCA, respectively ( P < 0.001 for all). Primary sclerosing cholangitis was more strongly associated with perihilar (AOR = 453, 95% CI 104‐999) than intrahepatic (AOR = 93.4, 95% CI 27.1‐322) or distal (AOR = 34.0, 95% CI 3.6‐323) CCA, whereas diabetes was more associated with distal (AOR = 4.2, 95% CI 2.5‐7.0) than perihilar (AOR = 2.9, 95% CI 2.2‐3.8) or intrahepatic (AOR = 2.5, 95% CI 2.0‐3.2) CCA. Cirrhosis not related to primary sclerosing cholangitis was associated with both intrahepatic and perihilar CCA, with similar AORs of 14. Isolated inflammatory bowel disease without primary sclerosing cholangitis was not associated with any CCA subtype. Conclusions : Aspirin use was significantly associated with a 2.7‐fold to 3.6‐fold decreased risk for the three CCA subtypes; our study demonstrates that individual risk factors confer risk of different CCA subtypes to different extents. (Hepatology 2016;64:785‐796)